Marketing Healthy Food in an African City: Consumer Motivations for Adopting Orange-Fleshed Sweet Potato in Maputo, Mozambique - Brouwer, R. (SAGE Publications, 2021)
Since the late 1990s, the International Potato Center has promoted orange-fleshed sweet potato (OFSP) cultivars in Mozambique as a healthy food, emphasizing its capacity to reduce the prevalence of vitamin A deficiency among mothers and young children. This article seeks to reveal why consumers in Maputo, the capital city of Mozambique, adopt or reject OFSP looking at the role of food systems and consumer characteristics in access and acceptance of healthy food and at the positioning OFSP on the market in terms of lifestyle and need satisfaction.The results of 255 street interviews confirm that OFSP is widely known. Information reaches people mainly via informal channels (relatives and retailers). Nonadoption is the result of the positioning of OFSP as food for young children and sick people. The OFSP appeals most to the hedonistic and conservative lifestyle segments. Adoption is associated with the perception of OFSP as a source of vitamins that builds up muscles and improves physical appearance and self-fulfillment. While women are typically responsible for domestic tasks, male adopters emphasize the role of OFSP in family health and well-being more than female adopters. This first attempt to understand the marketing of healthy food in Mozambique exposes many similarities between the urban consumers in Maputo and those in developed countries. The results indicate that future marketing should exploit informal channels such as vendors and emphasize its nutritious value for all consumers instead of focusing on mothers and young children.